APPRAISING THE TECHNOLOGICAL PERSPECTIVE OF CRM: A CASE STUDY OF SEVEN-UP BOTTLING COMPANY PLC APAPA REGION LAGOS, NIGERIA - Olorunleke, Gabriel Kolade (European Scientific Journal, ESJ, 2013)
Technology is an indispensable ingredient of the customer relationship. The technology requirement needs to be carefully thought out to develop a single source of customer information that is interactive, fully integrated and enterprise wide and to ensure the use of innovative technology to support customer channels and delivery of value. As a result of the above, this paper tends to appraise the effectiveness of the CRM technology using seven –up Bottling company Apapa, Lagos as a case study This takes into consideration that CRM is organization specific. The study uses a five point liket scale to elicit information from salesmen. The study collected data from 45 respondents as uses simple frequency distribution analysis. The study concludes that efforts should be made to first establish sales as Marketing process and strategies that would support customers’ strategy before we talk on the appropriateness of the technology.